2014
DOI: 10.1021/jf403586t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Evaluation, and Structure–Activity Relationship of α-Pinene Derivatives

Abstract: Several (+)- and (-)-α-pinene derivatives were synthesized and evaluated for their antimicrobial activity toward Gram-positive bacteria Micrococcus luteus and Staphylococcus aureus, Gram-negative bacterium Escherichia coli, and the unicellular fungus Candida albicans using bioautographic assays. (+)-α-Pinene 1a showed modest activity against the test organisms, whereas (-)-α-pinene 1b showed no activity at the tested concentration. Of all the α-pinene derivatives evaluated, the β-lactam derivatives (10a and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 33 publications
(63 reference statements)
4
34
0
2
Order By: Relevance
“…It is present in EOs of various plant species and has been recognized for its potent antimicrobial activity. Recent studies have shown that it effectively inhibits P450 2B [21]. In addition, this compound complies with the criteria described by Lipinsky related to the affinity for biological membranes and absorption, and therefore, related to its activity: it has a molecular weight less than 500 (136), has an index of lipophilicity (logP) equal to 4.3 and a number of groups which can aureus, but the results differ in the activity against E. coli.…”
supporting
confidence: 66%
“…It is present in EOs of various plant species and has been recognized for its potent antimicrobial activity. Recent studies have shown that it effectively inhibits P450 2B [21]. In addition, this compound complies with the criteria described by Lipinsky related to the affinity for biological membranes and absorption, and therefore, related to its activity: it has a molecular weight less than 500 (136), has an index of lipophilicity (logP) equal to 4.3 and a number of groups which can aureus, but the results differ in the activity against E. coli.…”
supporting
confidence: 66%
“…So, α‐pinene which is the most abundant component in J . excelsa essential oil might play an important role in the antifungal activity of the oil (Dhar et al, ). C .…”
Section: Resultsmentioning
confidence: 99%
“…While J. excelsa EO exhibited only a moderate antimicrobial activity against the two S. cerevisiae yeasts strains A9 (MIC 2.5 μL/mL) and EC1118 (MIC 5 μL/mL). So, α-pinene which is the most abundant component in J. excelsa essential oil might play an important role in the antifungal activity of the oil(Dhar et al, 2014).C. zeylanicum, C. capitatus, and O. syriacum EOs showed a significant antimicrobial activity against yeasts strains with MIC values ranging from 0.039 to 0.625 μL/mL.…”
mentioning
confidence: 99%
“…Cumin EO is reported to have antibacterial and antifungal activities (Chaudhary et al, ; Nisha et al, ). The antimicrobial activity of EO from cumin can be correlated to its chemical composition as β‐pinene, o ‐cymene, δ‐carene, and cuminaldehyde, p ‐cymen‐7‐ol, the major compounds in EO from SC and FC, are reported to possess antimicrobial activities (Custodio, Ribeiro, Silva, Machado, & Sousa, ; Dhar et al, ).…”
Section: Resultsmentioning
confidence: 99%